THE PSYCHOTHERAPIST’S SOCIAL ROLE UNDER A DIALOGICAL PERSPECTIVE: A STUDY OF THE PERSONAL CONSTRUCTION OF ‘I AS PSYCHOTHERAPIST’ - Tavares, Sofia (2013)
To become a psychotherapist is a self-organizing challenge for anyone who assumes that role, involving a dynamic dialogical interplay between social expectations and personal features. This involves subjective and intersubjective processes in which self-image (or “internal I-position”) emerges as co-relative others’ images (or “external I-positions”). The classical distinction between the motives of agency and communion is considered here a valuable theoretical tool for this dialogical approach, because it may help to distinguish and classify diversity in terms of two kinds of orientations towards clients: one more self-centred (focused on the therapist’s abilities and power) and the other a more other-centred (focused on the contact and empathy with the client). Following these assumptions, clearly rooted in a dialogical approach of self-identity, we analyse the discourse of three psychotherapists about two different clients (one referred to as a “positive client” and another referred to as a “negative client”). The results suggest that this adaptation is a very dynamic process and that different therapists create different meanings to their occupational role. Moreover, this analysis also allows a distinction between those different selfimages in terms of their global orientation. One of the therapists seems to engage in self-organization processes focused in self-needs, other seems focused on client’s needs and the third seems to keep a balance between thosetwo orientations. The implication of these results for future research and their practical and theoretical implications are discussed.